COMPARATIVE CLINICAL AND PHARMACOLOGICAL CHARACTERISTICS OF HYPOTENSIVE EFFICACY AND SAFETY OF SHORT AND PROLONGED ACTION SLOW CALCIUM CHANNELS BLOCKERS: NIFEDIPINE, CORDAFLEX-RETARD AND NIFECARD XL IN PATIENTS WITH MILD TO MODERATE ARTERIAL HYPERTENSION - V. G. Kukes; A. K. Starodubtsev; G. V. Ramenskaya; E. A. Toporova; I. S. Lipatova (Российский кардиологический журнал)
An experience of evaluation of the following drugs is provided: nifedipine (Corinfar), Nifecard XL and Cordaflex-retard in treatment of patients with mild to moderate arterial hypertension. The aim of the study was to compare hemodynamics values of the drugs with the results of their pharmacokinetic studies in single and course intake. An open label randomized method of drug administration was used. At the same time a comparative evaluation of adverse effects of studied drugs was made.In the group of patients receiving Nifecard XL in single intake, a moderate increase of antihypertensive effect was observed for 1, 5-2 hours, lasting for 6-8 hours, corresponding to gradually increasing and, respectively, maintained in the stable way drug concentration in blood plasma; no sudden decrease of blood pressure and increase of heart rate was observed. Tolerability of Nifecard XL was assessed as good.With single intake the group of patients taking Cordaflex-retard demonstrated a rapid increase of antihypertensive effect (for 1-1, 5 hours), but a more short-term maintenance explained by less absorption rate and a more rapid excretion as compared to Nifecard XL. With a course intake, following a dose correction, a sustained maintenance of normal BP values if a twice daily regimen is adhered to.